Creditor Protection and Legal Certainty in Loan Agreement Defaults: Perlindungan Kreditur dan Kepastian Hukum dalam Wanprestasi Utang Piutang - Kevin Anandita Rukmana; Gunawan Djajaputra (Indonesian Journal of Law and Economics Review, 2026)
General Background: Debt agreements are common civil legal relationships that may generate disputes when debtors fail to fulfill their obligations. Specific Background: In debt default cases, creditors require legal protection and legal certainty to secure their rights through available legal instruments. Knowledge Gap: Although civil law normatively regulates creditor protection, practical obstacles remain, including lengthy dispute settlement, high costs, inconsistent legal application, and ineffective execution of court decisions. Aims: This study analyzes legal protection and legal certainty for creditors in debt default agreements and examines the application of good faith and pacta sunt servanda in realizing creditor protection. Results: The findings show that civil law provides preventive and repressive protection through valid agreement requirements, clear rights and obligations, claims for performance, compensation, and agreement cancellation. Legal certainty is reflected in the binding force of valid agreements as law for the parties. However, protection has not been fully optimal in practice due to procedural and enforcement barriers. Good faith supports honest, fair, and reasonable conduct, while pacta sunt servanda affirms the obligation to honor valid agreements. Novelty: The study emphasizes the balanced application of good faith and pacta sunt servanda as the key to aligning legal certainty with justice in creditor protection. Implications: Stronger enforcement, clearer contractual drafting, and consistent judicial application are needed to realize creditor protection more optimally in debt default cases. Highlights: Civil law recognizes preventive and repressive safeguards for harmed parties. Court process duration, expenses, and execution barriers limit practical realization. Balanced contractual principles help align binding obligations with fairness. Keywords: Legal Protection, Legal Certainty, Breach of Contract